Understanding hepatitis - Aguinaldo, F. (Quezon City MMA Publications, 2002)
Aguinaldo aims to give students, professors, and the general public alike, information regarding hepatitis. This book contains fundamental information about hepatitis including its symptoms, diagnosis and cure. Prevention methods are also included in this manual.
Keywords: Hepatitis -- Handbooks, manuals, etc; Hepatitis, Viral